Sarita, the Carlist - Marchmont, Arthur W., 1852-1923; Murray Smith, D., 1865-1952 (Salt Lake City, UT : Project Gutenberg, 2016)
"Sarita, the Carlist" by Arthur W. Marchmont is a novel written in the early 20th century. The story revolves around Ferdinand Carbonnell, who finds himself embroiled in the complicated political intrigues of Spain as he navigates familial relationships and the dangerous world of the Carlists. The narrative suggests a rich blend of romance, political drama, and personal conflict as Ferdinand encounters his cousin Sarita Castelar and must grapple with unexpected familial obligations and a tumultuous past. The opening of the novel introduces Ferdinand Carbonnell, who faces the repercussions of a woman$1 (Bs preference as his family plots for a match between him and a wealthy widow. Suddenly thrust into a diplomatic role, he discovers a deeper familial connection to the Quesadas in Madrid and is drawn into a web of political secrecy and familial history, including the troubling legacy of his uncle. Shortly after his arrival, he is mistaken for a Carlist leader and nearly suffers serious consequences due to a case of mistaken identity. It is Sarita Castelar, the stunning cousin he meets, who rescues him from a dire situation, hinting at their shared family ties and the looming political machinations that will entwine their fates. The tension between personal aspiration and political loyalty sets the stage for this engaging tale of love, loyalty, and upheaval. (This is an automatically generated summary.)s
Release date is 2016-11-18
Produced by Al Haines
Keywords: Love stories; Adventure stories; British -- Spain -- Fiction; Spain -- History -- 19th century -- Fiction